Spared musical abilities in a conductor with global aphasia and ideomotor apraxia. Issue 5 (May 1985) - Basso, A; Capitani, E
Abstract : A conductor suddenly developed global aphasia and severe ideomotor apraxia as a result of an infarct in the territory of the left middle cerebral artery. Although aphasia and apraxia remained unchanged during the following six years, his musical capacities were largely spared and he was still able to conduct. This case provides some evidence in favour of right hemisphere dominance for music.